2015
DOI: 10.1098/rsob.150094
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lamin properties and functions: does phosphorylation do it all?

Abstract: The main functions of lamins are their mechanical and structural roles as major building blocks of the karyoskeleton. They are also involved in chromatin structure regulation, gene expression, intracellular signalling pathway modulation and development. All essential lamin functions seem to depend on their capacity for assembly or disassembly after the receipt of specific signals, and after specific, selective and precisely regulated interactions through their various domains. Reversible phosphorylation of lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 133 publications
(252 reference statements)
0
62
0
Order By: Relevance
“…Seeking to understand the further‐reaching consequences of this phosphorylation step, it has been proposed on the basis of lamin A coil 2B dimeric crystal structures that phosphorylation may interfere with electrostatic interactions . This scenario, however, was challenged by the identification of the phosphorylation‐dependent lamin binding of the peptidyl‐prolyl cis/trans isomerase Pin1 and the functional validation that strongly supported a mode of Pin1‐induced conformational change facilitating lamina disassembly . Recently, a combined strategy of pharmacological Pin1 inhibition and Pin1 knockout provided conclusive evidence that Pin1 promotes the disassembly of the nuclear lamina during HCMV replication …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeking to understand the further‐reaching consequences of this phosphorylation step, it has been proposed on the basis of lamin A coil 2B dimeric crystal structures that phosphorylation may interfere with electrostatic interactions . This scenario, however, was challenged by the identification of the phosphorylation‐dependent lamin binding of the peptidyl‐prolyl cis/trans isomerase Pin1 and the functional validation that strongly supported a mode of Pin1‐induced conformational change facilitating lamina disassembly . Recently, a combined strategy of pharmacological Pin1 inhibition and Pin1 knockout provided conclusive evidence that Pin1 promotes the disassembly of the nuclear lamina during HCMV replication …”
Section: Resultsmentioning
confidence: 99%
“…72,74 Site-specific phosphorylation of lamins A/C at Ser22 is known to mediate nuclear lamina disassembly both during herpesviral nuclear egress and cellular mitosis. 44,60,118 Seeking to understand the further-reaching consequences of this phosphorylation step, it has been proposed on the basis of lamin A coil 2B dimeric crystal structures that phosphorylation may interfere with electrostatic interactions. 119 cles.…”
Section: Concerted Action Between Various Regulatory Proteins Assocmentioning
confidence: 99%
“…To address how nuclear lamin B was disassembled in NETotic nuclear envelope rupture, we found that cytosolic PKCα was translocated to nucleus where PKCα may mediate nuclear lamin B phosphorylation, disassembly, and nuclear disintegration, similar to the context of mitosis (Mall et al, 2012), and viral infection (Park and Baines, 2006). The time-course experiments In several other contexts of the nuclear envelope rupture (Kuga et al, 2010;Machowska et al, 2015;Shimizu et al, 1998)…”
Section: Nuclear Translocation and Phosphorylation Of Pkcα During Neumentioning
confidence: 97%
“…To explore the causal role of lamin B phosphorylation, we found that pre-treatment of human neutrophils with Go6976, a selective inhibitor of conventional PKC, attenuated PKCα phosphorylation in human neutrophils that were stimulated by PMA ( Fig. 5A) To further define the causal role of PKCα-mediated lamin B phosphorylation in NETosis, we made mutations at the PKCα-consensus serine phosphorylation sites (S395, S405, S408) of lamin B (Hocevar et al, 1993;Machowska et al, 2015;Mall et al, 2012) by replacement of serine (S) with alanine (A), which will prevent PKCα-mediated serine phosphorylation at lamin B. Mutants with single or multiple mutations (S395A, S395A/S405A, S395A/S405A/S408A) ( Fig. 5D) were made.…”
Section: Pkcα Serine Phosphorylation Sites In Lamin B Attenuates Neumentioning
confidence: 99%
“…The tail domain of lamins contains an Ig fold, an unstructured region, a nuclear localization signal (NLS) and a CaaX motif. 4,5 In mammals, lamins are encoded by 3 genes, which give rise to 4 major isoforms. Lamins A and C (A type lamins) are encoded by the LMNA gene through alternative splicing, and are mostly expressed in differentiated cells.…”
Section: Introductionmentioning
confidence: 99%